1990
DOI: 10.1111/j.1365-2621.1990.tb06762.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryoprotective Effects of Lactitol, Palatinit and Polydextrose® on Cod Surimi Proteins during Frozen Storage

Abstract: The cryoprotective effects of lactitol dihydrate, Polydextrose@ and Palatinit (Isomalt) at 8% w/w in cod-surimi were compared to an industrial control containing a sucrose/sorbitol 1:l mixture and a control without additive. Surimi was stored at -20°C for 12 wk and examined for freeze-induced protein changes every 2 wk by salt extractable protein and differential scanning calorimetry analyses: Palatinit@, lactitol and Polydextrose@ stabilized surimi proteins equally well as did the sucrose/sorbitol mixture. Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
3
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 19 publications
7
52
3
4
Order By: Relevance
“…Similar results was reported by Kijowski and Richardson (1996) for washed mechanically deboned poultry meat, this could be explained by concentration of myofibrillar protein by washing and different pH and ionic environment when compared to the raw state of muscle (Wright and Wilding 1984;Xiong et al 1987;Lesiow and Xiong 2001). Analysis of variance of myosin T p showed that myosin's T p varied significantly (P<0.05) as a function of mass fraction of trehalose, but not as of frozen storage time (Sych et al 1990;Herrera et al 2001) (Table 1). These shifts in T p of myosin to the higher values as the mass fraction of trehalose increases can be interpreted as a stabilization of myofibrillar proteins since a higher temperature was required to denature these proteins (Sych et al 1990;Sych et al 1991).…”
Section: Differential Scanning Calorimetrysupporting
confidence: 73%
See 3 more Smart Citations
“…Similar results was reported by Kijowski and Richardson (1996) for washed mechanically deboned poultry meat, this could be explained by concentration of myofibrillar protein by washing and different pH and ionic environment when compared to the raw state of muscle (Wright and Wilding 1984;Xiong et al 1987;Lesiow and Xiong 2001). Analysis of variance of myosin T p showed that myosin's T p varied significantly (P<0.05) as a function of mass fraction of trehalose, but not as of frozen storage time (Sych et al 1990;Herrera et al 2001) (Table 1). These shifts in T p of myosin to the higher values as the mass fraction of trehalose increases can be interpreted as a stabilization of myofibrillar proteins since a higher temperature was required to denature these proteins (Sych et al 1990;Sych et al 1991).…”
Section: Differential Scanning Calorimetrysupporting
confidence: 73%
“…Analysis of variance of myosin T p showed that myosin's T p varied significantly (P<0.05) as a function of mass fraction of trehalose, but not as of frozen storage time (Sych et al 1990;Herrera et al 2001) (Table 1). These shifts in T p of myosin to the higher values as the mass fraction of trehalose increases can be interpreted as a stabilization of myofibrillar proteins since a higher temperature was required to denature these proteins (Sych et al 1990;Sych et al 1991). Highest shift in T p of myosin shows the samples of WCM mixed with 10% of trehalose for all storage time intervals.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%
See 2 more Smart Citations
“…AFS.2018.0537 processability (MacDonald et al, 2005). Measurements of myofibrillar protein solubility SEP (Salt extractable protein), Ca 2+ ATP-ase activity, unfrozen water by Nuclear Magnet Resonance (NMR), and transition temperatures and enthalpy of myofibrillar proteins by differential scanning calorimetry (DSC) are the most commonly used instrumental methods for the determination of the cryoprotective effects of added substances (Kijowski and Richardson, 1996;Park et al, 1993;Stangierski and Kijowski, 2008;Sych et al, 1990). DSC is an often used as instrumental method for studying thermal behaviour of muscle proteins (Findlay and Barbut, 1990).…”
Section: Introductionmentioning
confidence: 99%